Ultra-mini-PCNL using the urological Dyna-CT in small infants: a single-center experience : urology : original paper - Grüne, Britta; Rassweiler-Seyfried, Marie-Claire; Müller, Kim; Nuhn, Philipp; Michel, Maurice Stephan; Younsi, Nina; Stein, Raimund; Herrmann, Jonas (International urology and nephrology, 2022)
To analyze and share our experience with ultra-mini-PCNL using the urological Dyna-CT in small infants. Methods A retrospective analysis was performed on all infants younger than 3 years of age who underwent ultra-mini-PCNL at our institution since 2016. Operating time, luoroscopy time, dose area product (DAP), stone-free status, intra- and postoperative complications and the duration of hospital stay were analyzed. Results A total of nine interventions conducted on eight children were evaluated. The mean age of infants was 22.8 ± 11.9 months. The mean operation time and the mean fluoroscopy time were 119.2 ± 51.8 min, and 190.4 ± 93.8 s, respectively. The mean DAP was 11.4 ± 6.9 μGym 2 and the stone clearance at 3 months was 87.5%. No major postoperative complications were assessed, and no transfusion was given. The mean hospital stay was 4 (IQR 3–6) days. Conclusion Ultra-mini-PCNL utilizing the urological Dyna-CT can safely and effectively be performed in small infants with kidney stones. In this setting, the urological Dyna-CT allows for a very low radiation exposure.